2018
DOI: 10.3390/fi10080079
|View full text |Cite
|
Sign up to set email alerts
|

Queue Spillover Management in a Connected Vehicle Environment

Abstract: To alleviate the queue spillovers at intersections of urban roads during rush hours, a solution to the cross-spill problem based on vehicle networking technologies is proposed. This involves using connected vehicle technology, to realize the interactive information on vehicle and intersection signal control. The maximum control distance between intersections is determined by how vehicles are controlled and would travel in that connected environment. A method of calculating overflow tendency towards intersectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is observed that the proposed protocol gives optimum performance under the defined scenario and assumptions being made. In Table 4, we expand the security performance analysis for some more available schemes [43][44][45] and tabulate the findings. Such an analysis is believed to help future researchers to identify the protocols specific to their area of study.…”
Section: Discussion and Comparative Summarymentioning
confidence: 99%
“…It is observed that the proposed protocol gives optimum performance under the defined scenario and assumptions being made. In Table 4, we expand the security performance analysis for some more available schemes [43][44][45] and tabulate the findings. Such an analysis is believed to help future researchers to identify the protocols specific to their area of study.…”
Section: Discussion and Comparative Summarymentioning
confidence: 99%
“…By using the information interaction between vehicle and intersection signal control [30], the overflow trend can be identified by the all vehicles' position data, and the overflow prevention can be realized by combining vehicle speed control and signal control. is kind of advanced detection method requires the utilization of V2I and Internet of Vehicles.…”
Section: Overflow Control Based On Internet Of Vehicles Technologymentioning
confidence: 99%
“…Estimation. To estimate the queue length in each direction of the intersection with single detector data [24][25][26][27][28][29][30] or multiple source-detector data [31,32] or vehicle road collaboration data [33], the queue length is used as the basis for traffic state recognition. It can be judged through checking whether the queue length reaches the threshold.…”
Section: Traffic State Recognition Based On Queue Lengthmentioning
confidence: 99%